Molecular and clinical implementations of ovarian cancer mouse avatar models - Zayed, Amira A.; Mandrekar, Sumithra J.; Haluska, Paul (Chinese Clinical Oncology; Vol 4, No 3 (September 25, 2015): Chinese Clinical Oncology (Clinical Trials in the Genome Era—Study Designs and Endpoints, Practical Considerations - Guest Editors: Daniel Sargent, Sumithra Mandrekar and Axel Grothey), 2015)
Innovation in oncology drug development has been hindered by lack of preclinical models that reliably predict clinical activity of novel therapies in cancer patients. Increasing desire for individualize treatment of patients with cancer has led to an increase in the use of patient-derived xenografts (PDX) engrafted into immune-compromised mice for preclinical modeling. Large numbers of tumor-specific PDX models have been established and proved to be powerful tools in pre-clinical testing. A subset of PDXs, referred to as Avatars, establish tumors in an orthotopic and treatment naïve fashion that may represent the most clinical relevant model of individual human cancers. This review will discuss ovarian cancer (OC) PDX models demonstrating the opportunities and limitations of these models in cancer drug development, and describe concepts of clinical trials design in Avatar guided therapy.